A Review of Properties, Engine Performance, Emission Characteristics and Material Compatibility Biodiesel From Waste Cooking Oil (WCO) - Suherman, Suherman; Abdullah, Ilmi; Sabri, M.; Turmuzi, Muhammad; Silitonga, Arridina Susan; Dharma, Surya; Yusfiani, Marnida (Automotive Laboratory of Universitas Muhammadiyah Magelang in collaboration with Association of Indonesian Vocational Educators (AIVE), 2023)
Biodiesel is one of the renewable energy sources, non-fossil. The chosen feedstock should ideally be low-cost. Using waste cooking oil can reduce synthetic biodiesel's price by up to 70%. However, biodiesel has the advantage of lower heating value and higher density, causing increased fuel consumption and NOx emissions. Biodiesel has physicochemical properties such as a more significant cetane number than fossil diesel, a high flash point, and the absence of sulfur. This study identifies the potential availability of WCO as biodiesel and summarizes recent studies on the physiochemical properties of WCO biodiesel. This study also aims to clarify the use of WCO biodiesel on engine performance and exhaust emission characteristics (H.C., CO, CO2, NOx) when this biodiesel is used. Engine type and biodiesel ratio were identified for all articles. This study also discusses the effect of adding nanoparticles on engine performance and exhaust emissions in WCO biodiesel. This study also clarifies material compatibility (corrosion, wear, and friction). The corrosion rate in various types of materials and corrosion testing methods. Finally, this paper presents the opportunity for WCO biodiesel to be very feasible to reduce fossil diesel use.